Penerapan Teknologi Green House Kopi Arabika dalam Upaya Kemandirian Ekonomi Desa Sridadi Kecamatan Sirampog - sutarmin; Siti Badiatul Umroh; Ivan Akmal Nur; Undri Rastuti; Kharisma Nurmeilinda; Syahrul Saputra; Anjani, Mia (Jurnal Pengabdian kepada Masyarakat Nusantara, 2024)
Coffee is one of the top 3 potential regional superior products in Brebes Regency, in addition to salted eggs and shallots. Sirampog sub-district is the most dominant sub-district that produces Arabica type coffee because Sirampog sub-district is at an altitude above 1000 meters above sea level. The lack of post-harvest technology and conventional coffee processing are the main obstacles for partners in maintaining quality and increasing quantity. This has become a problem for partners in meeting the increasing market demand. The process of drying the initial drying of coffee which is done traditionally requires a lot of energy, is impractical, has the potential to reduce the flavor of coffee due to odor absorption and is difficult to do in the rainy season. Based on these conditions, the village empowerment team (PDB) of Universitas Peradaban and Unsoed funded by DRTPM in the first year (2024) conducted community service through various trainings, workshops and appropriate technology grants. In the implementation of appropriate technology, green house technology measuring 7 m x 10 m2 has been granted with a drying capacity of 2 tons. The drying results are efficient because farmers no longer need to lift and dry the coffee in the afternoon or when it rains. Farmers only need to turn it over so that the dryness is evenly distributed. The greenhouse system also dries faster because the heat is stored and trapped, and the capacity increases 3 times because the drying is arranged in 3 layers.